2023
DOI: 10.3390/vaccines11040810
|View full text |Cite
|
Sign up to set email alerts
|

Association between the COVID-19 Vaccine and Preventive Behaviors: Panel Data Analysis from Japan

Abstract: The coronavirus (COVID-19) vaccine is key to reducing the probability of contracting COVID-19. The vaccine is generally known to prevent severe illness, death, and hospitalization as a result of the disease and for considerably reduce COVID-19 infection risk. Accordingly, this might significantly change an individual’s perceived risk of altering everyday behaviors. For instance, the proliferation of vaccination is anticipated to reduce preventive behaviors such as staying at home, handwashing, and wearing a ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Moreover, one study from China reported that the protective behaviors of Chinese university students weakened after vaccination [ 8 ]. In contrast, using Japan’s longitudinal data, Yamamura et al [ 9 ] reported that vaccinating led to staying home more but did not change handwashing and mask-wearing practices. Previous findings further indicated that vaccinated Canadian individuals were more likely to report engaging in distancing, wearing masks, and maintaining hand hygiene compared with unvaccinated individuals [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, one study from China reported that the protective behaviors of Chinese university students weakened after vaccination [ 8 ]. In contrast, using Japan’s longitudinal data, Yamamura et al [ 9 ] reported that vaccinating led to staying home more but did not change handwashing and mask-wearing practices. Previous findings further indicated that vaccinated Canadian individuals were more likely to report engaging in distancing, wearing masks, and maintaining hand hygiene compared with unvaccinated individuals [ 10 ].…”
Section: Introductionmentioning
confidence: 99%